Status of vaccine research and development for enterotoxigenic Escherichia coli. Issue 26 (3rd June 2016) - Bourgeois, A. Louis; Wierzba, Thomas F.; Walker, Richard I.
Highlights: ETEC is a top cause of diarrhea in children and travelers to low-resource countries. Models suggest ETEC vaccines would be cost-effective and have a beneficial impact. ETVAX is the most advanced ETEC candidate; a subunit approach is also in clinical development. Ongoing research is evaluating the impact of adjuvants and new "omics" technologies. Limited financing for ETEC vaccine may be enhanced by combined vaccine formulations. Abstract: Enterotoxigenic Escherichia coli (ETEC) is one of the most common bacterial causes of diarrhea-associated morbidity and mortality, particularly among infants and young children in developing countries. Still, the true impact on child and traveler health is likely underestimated. There are currently no licensed vaccines for ETEC, but studies indicate high public health impact, cost-effectiveness, and feasibility of immune protection through vaccination. ETEC vaccine development remains a World Health Organization priority. Traditionally, ETEC vaccine development efforts have focused on inducing antitoxin and anticolonization antigen immunity, as studies indicate that antibodies against both antigen types can contribute to protection and thus have potential for vaccines. Leading cellular vaccine candidates are ETVAX (a mixture of four inactivated strains) and ACE527 (a mixture of three live attenuated strains), both of which have been found to be safe and immunogenic in Phase 1/2 trials. ETVAX is the furthest along in development with descending-age studies already underway in Bangladesh. Other ETEC vaccine candidates based on protein subunits, toxoids (both LT and ST), or novel, more broadly conserved ETEC antigens are also under development. Of these, a protein adhesin-based subunit approach is the most advanced. Impact and economic models suggest favorable vaccine cost-effectiveness, which may help expand market interest in ETEC vaccines. Combination vaccine formulations may help improve the economic case for development and use, and better point-of-care diagnostics will help to raise awareness of the true health burden of ETEC and highlight the potential public health benefit of ETEC vaccine introduction. Better diagnostics and vaccine demand forecasting will also improve vaccine development financing and support accelerated uptake once a licensed vaccine becomes available.